2001
DOI: 10.1086/321286
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative-Trait-Locus Analysis of Body-Mass Index and of Stature, by Combined Analysis of Genome Scans of Five Finnish Study Groups

Abstract: In recent years, many genomewide screens have been performed, to identify novel loci predisposing to various complex diseases. Often, only a portion of the collected clinical data from the study subjects is used in the actual analysis of the trait, and much of the phenotypic data is ignored. With proper consent, these data could subsequently be used in studies of common quantitative traits influencing human biology, and such a reanalysis method would be further justified by the nonbiased ascertainment of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
6
2

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 29 publications
(34 reference statements)
10
94
6
2
Order By: Relevance
“…The heritability of height for the eight groups varied from 0.75 to 0.98, which is compatible with previous reports. [4][5][6] For individual genome scans, the region showing the strongest evidence for linkage was found in GENOA European Americans, centered at 14q21.1(MLS ¼ 3.67 at marker D14S592 ) ( Table 2). The same region also showed evidence of linkage in SAPPHIRe Asians with a LOD ¼ 1.60.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heritability of height for the eight groups varied from 0.75 to 0.98, which is compatible with previous reports. [4][5][6] For individual genome scans, the region showing the strongest evidence for linkage was found in GENOA European Americans, centered at 14q21.1(MLS ¼ 3.67 at marker D14S592 ) ( Table 2). The same region also showed evidence of linkage in SAPPHIRe Asians with a LOD ¼ 1.60.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Genetic studies of adult height have revealed that it is normally distributed, suggesting that height could be affected by the interaction of multiple genetic and environmental factors. Compared with other complex traits, adult height can be measured easily and accurately, reducing error variance in the phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative traits such as height, body mass index, blood pressure, visual acuity, and psychometric measures, that are routinely gathered in many epidemiological and genetic studies beg for proper analysis (Perola et al 2001). Longitudinal data such as that collected in the Framingham Heart Study also await more sophisticated treatment (Kraft et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…GSMA needs at least one value of each study in each bin which is rarely the case if only interesting values are reported. However, more and more researchers distribute the detailed results of their analysis via the internet, such as NPL scores for each marker tested (as in a psoriasis scan by Nair et al 1997), where the multipoint statistics at regular intervals (as in a stature and BMI genome scan by Perola et al 2001) and the information content could be included. Besides, it is a long standing scientific tradition to retain data and intermediate results and to give other researchers the opportunity to verify the reported results by making materials and data available.…”
Section: Discussionmentioning
confidence: 99%